A Stable Cell Line Expressing Clustered AChR: A Novel Cell-Based Assay for Anti-AChR Antibody Detection in Myasthenia Gravis - Cai, Yu; Han, Lu; Zhu, Desheng; Peng, Jing; Li, Jianping; Ding, Jie; Luo, Jiaying; Hong, Ronghua; Wang, Kan; Wan, Wenbin; Xie, Chong; Zhou, Xiajun; et al. (Frontiers in Immunology, 2021)
Cell-based assays (CBAs) and radioimmunoprecipitation assay (RIPA) are the most sensitive methods for identifying acetylcholine receptor (AChR) in myasthenia gravis (MG). But CBAs are limited in clinical practice by transient transfection. We established a stable cell line (KL525) expressing clustered AChR by infecting HEK 293T cells with dual lentiviral vectors expressing the genes encoding the human AChR α1, β1, δ, ε and the clustering protein rapsyn. We verified the stable expression of human clustered AChR by immunofluorescence, immunoblotting, and real-time PCR. Fluorescence-activated cell sorting (FACS) was used to detect anti-AChR antibodies in 103 MG patients and 58 healthy individuals. The positive results of MG patients reported by the KL525 was 80.6% (83/103), 29.1% higher than the 51.4% (53/103) of RIPA. 58 healthy individuals tested by both the KL525 CBA and RIPA were all negative. In summary, the stable expression of clustered AChR in our cell line makes it highly sensitive and advantageous for broad clinical application in CBAs.